2019
DOI: 10.1103/physrevd.100.103008
|View full text |Cite
|
Sign up to set email alerts
|

Progress towards characterizing ultrahigh energy cosmic ray sources

Abstract: We use a multimessenger approach to constrain realistic mixed composition models of ultrahigh energy cosmic ray sources using the latest cosmic ray, neutrino, and gamma-ray data. We build on the successful Unger-Farrar-Anchordoqui 2015 (UFA15) model which explains the shape of the spectrum and its complex composition evolution via photodisintegration of accelerated nuclei in the photon field surrounding the source. We explore the constraints which can currently be placed on the redshift evolution of sources an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
73
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 74 publications
5
73
0
2
Order By: Relevance
“…Some cautionary comments on the illustrative model considered here are in order. The presence of a subdominant light component at the highest energies is not excluded by our data, see, e.g., [45]. Also, viable source scenarios can be found without resorting to a mixed composition with a rigidity-dependent maximum energy if, for instance, predominately heavy (Si to Fe) nuclei are accelerated and photodisintegrate in the source environment [46] or en route to Earth [47,48].…”
mentioning
confidence: 77%
“…Some cautionary comments on the illustrative model considered here are in order. The presence of a subdominant light component at the highest energies is not excluded by our data, see, e.g., [45]. Also, viable source scenarios can be found without resorting to a mixed composition with a rigidity-dependent maximum energy if, for instance, predominately heavy (Si to Fe) nuclei are accelerated and photodisintegrate in the source environment [46] or en route to Earth [47,48].…”
mentioning
confidence: 77%
“…The dN/dX max tail depends on the cosmic ray mass composition. The composition above 40 EeV is modeled here with two simple representative scenarios guided by the cosmic ray composition analysis described in [65]. A conservative UHECR composition scenario with 10% protons and 90% nitrogen has a 20% proton fraction in the high X max tail.…”
Section: Poemma Uhecr Performancementioning
confidence: 99%
“…In fact, Ref. [16] has shown that, for the specific model discussed there, an additional proton component even improves the fit to the UHECR spectrum and composition.…”
Section: Introductionmentioning
confidence: 99%
“…In, e.g., Refs. [12,13,14,15,16] the UHECR spectrum and composition (assuming specific hadronic interaction modes) are fitted and corresponding cosmogenic neutrino fluxes are obtained under the assumptions of a continuous distribution of identical sources and rigidity-dependent maximum energies. In most cases these combined fits find as a best fit a relatively hard spectral index (α 1.3), a composition dominated by nuclei with a charge Z ≥ 6 and a relatively low maximum rigidity (R max ≡ E max /Z 7 EV).…”
Section: Introductionmentioning
confidence: 99%